Pengaruh Pengaruh Penguatan Personal Mastery dan Shared Vision terhadap Budaya Organisasi di Sekolah Dasar Kecamatan Jerowaru Lombok Timur: Personal Mastery, Shared Vision dan Budaya Organisasi - Pashurrahman; Jabar, Cepi Safruddin Abdul; Widiyan, Agung Purwa; Panjaitan, Rizki Ajhari (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to analyze the influence of strengthening personal mastery and shared vision on organizational culture in elementary schools. The research is grounded in the premise that a strong organizational culture is essential for fostering a conducive learning environment and enhancing the quality of education. A quantitative approach with a causal associative design was employed, involving 233 teachers from 46 public elementary schools in Jerowaru District, East Lombok Regency. The sample was selected using proportional stratified random sampling. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability. Multiple linear regression analysis was used to examine the relationships among variables. The results reveal that both personal mastery and shared vision have a significant effect on organizational culture, both partially and simultaneously. The significance values were 0.004 for personal mastery and 0.000 for shared vision. The coefficient of determination (R²) was 0.455, indicating that 45.5% of the variance in organizational culture is explained by these two variables. These findings highlight the importance of developing teachers’ individual capacities and aligning collective vision as strategic efforts to build adaptive, collaborative, and sustainable school organizational cultures. The findings can serve as a reference for school leaders and policymakers in designing teacher professional development programs and strengthening a shared vision to build adaptive and sustainable school organizational cultures.